Rekonstruksi Peradaban Islam Melalui Spirit Iqra’ - Mohammad Aziz (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
The problem of reconstructing Islamic civilization is not an easy matter. So far, it has seen signs toward the change. However, the changes that occur also still have no great effect on the current Islamic civilization. Therefore, to realize it, it is necessary to have a great motivation as the driving spirit to improve the work ethic of Muslims, especially in terms of science and technology development. Highlighting such a thing, through the spirit of iqra' is one effective way to arouse the spirit of Muslims in order to reconstruct civilization, especially in terms of science and technology development.